EFSUMB Recommendations and Clinical Guidelines for Intestinal Ultrasound (GIUS) in Inflammatory Bowel Diseases - Maconi, Giovanni; Nylund, Kim; Ripolles, Tomas; Calabrese, Emma; Dirks, Klaus; Dietrich, Christoph F.; Hollerweger, Alois; Sporea, Ioan; Saftoiu, Adrian; Maaser, Christian; Hausken, Trygve; Higginson, Antony P.; Nürnberg, Dieter; Pallotta, Nadia; Romanini, Laura; Serra, Carla; Gilja, Odd Helge (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
The accuracy and usefulness of gastrointestinal ultrasound (GIUS) for detecting activity and complications of inflammatory bowel diseases (IBD), has been reported in studies, promoting this technique as an important tool for the management of IBD patients. Whilst well recognised by international guidelines, standardization and general agreement in the definition of the luminal and extra-intestinal features, still need to be well defined.A task force group of 17 experts in GIUS faced this issue, by developing recommendations and clinical guidelines for the use of GIUS in IBD, under the auspices of EFSUMB. This article presents the consensus on the current data on sonographic features of IBD and summarises the accuracy of different sonographic modalities for the management of IBD patients.
Keywords: Gastrointestinal tract; inflammatory bowel diseases; guidelines; ultrasound; Crohn’s disease; ulcerative colitis; IBD; ultrasonography